Beyond threats, we need more information about action – how individuals see themselves (or not) in complex social-ecological systems - Waters, Y.; Thompson, K.; Wilson, K.; Dean, A. (Elsevier, 2025)
In the face of intersecting environmental crises such as climate change, biodiversity loss, and pollution, urgent action on all fronts is critical for a sustainable future. However, the complexity of these challenges can make it difficult for individuals to understand their role and identify meaningful actions. Little is known about how people perceive these interconnected social-ecological systems or their capacity to influence them. This study uses mental models to explore how individuals understand environmental threats and personal actions which can mitigate these threats within complex systems, using the Great Barrier Reef (GBR) as a case study. It also examines how communication approaches can shape these understandings. We conducted semi-structured interviews with Australian residents (n = 16) to elicit their mental models of environmental threats and actions in the context of the GBR. We also exposed participants to information highlighting either (i) part of the system, the impacts of climate change on the GBR, or (ii) multiple parts of the system (i.e., multiple interconnected threats such as water quality, overfishing etc.) to understand whether different information influenced existing mental models. Both quantitative and qualitative analyses were employed to assess participants’ existing mental models and the impact of the information presented. We found that while participants demonstrated a reasonable understanding of environmental threats, they lacked a strong understanding of actions to address them. Climate change information allowed some participants to identify new actions, but overall, both messages reinforced existing perspectives. Participants tended to perceive themselves as consumers within the system rather than agents of change. Insights from this study can guide policymakers in designing public communication strategies that build procedural knowledge and encourage the systems thinking needed to support the delivery of current environmental targets and initiatives.